Адаптивна робастна система регулювання енерготехнологічних об’єктів - Шуть, О. Ф.; Тришкін, В. Я.; Блонський, С. Д. (Видавництво Львівської політехніки, 2011)
In the article a approach is described to creation of the adaptive system the processes of heat exchange of oil industry enterprise on the basis of information about the dynamic state of object.
Keywords: адаптивна система; теплові процеси; робастність; динамічні властивості